Second first impressions [compact disc, unabridged] : a novel - Thorne, Sally, 1981- (Harper Audio, 2021)
Ruthie Midona will work in Providence's front office, and be at the Parloni's beck and call, forever. That's sort of her life plan. If Ruthie can run the place in her almost-retired bosses' absence, with no hijinks/hiccups, she has a shot at becoming the new manager. She might also be able to defend her safe little world from Prescott Development, the new buyer of the prime site. Teddy Prescott devotes his life to sleeping, tattooing, and avoiding seriousness. When Teddy needs a place to crash, he makes a deal with his developer dad. Teddy can stay in one of Providence's on-site maintenance cottages, right next door to an unimpressed Ruthie, but only if he works there and starts to grow up. Ruthie knows how this sweetly selfish rich boy can earn his keep, and be out of her hair in under a week. After all, there is a position vacant.